Uses and gratifications : perceptions, perspectives and patterns of behavior of students in selected secondary schools in Urban Kuching with regard to the use of the computer - Abang Sardon, Bin Abang Haji Hashim (Universiti Malaysia Sarawak (UNIMAS), 2000)
The purpose of this study was to determine the perceptions, perspectives and patterns of behavior of students in four selected secondary schools in urban Kuching with regard to the use of the computer and the gratification they derived from it .